AN ANALYSIS OF TRANSLATION METHODS USED IN ENGLISH-INDONESIAN TRANSLATION OF â€œTHE REAL PRINCESSâ€ BY HANS CHRISTIAN ANDERSEN - Muhammad Wahyu Shafrul Hidayat (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This research was the analysis of translation methods in the short story â€œThe Real Princessâ€ by Hans Christian Andersen translated from English to Indonesian by the participants of the research. The participants were selected from the translation II class of the 6th semester of the English Education Department of UNISMA using typical sampling of purposive sampling by questionnaire and interview. The data were collected from 4 participants' translation documentation with the A score from the translation I class and having some experience in translating. There were 22 sentences from the short story and a total of 88 data to be analyzed by the researcher. The analysis process was based on Newmarkâ€™s translation methods theory with qualitative descriptive methods that includes document analysis. As the results of the research, the researcher discovered 6 translation methods used by the participants to translate the short story. These translation methods were faithful, literal, communicative, semantic, free, adaptation. Faithful translation was the most used translation method among the 6 discovered translation methods.Â Keywords:Â Translation, Translation methods, Short story, Newmark